Kewenangan Penyelesaian Berkas Perkara Pidana Dalam Tahap Pra Penuntutan - I Gusti Agung Ayu Sita Anandia; I Made Arjaya; Ni Made Sukaryati Karma (Fakultas Hukum Universitas Warmadewa, 2019)
Pre prosecution is the authority of the public prosecutor to examine and study investigation and interrogation report before the investigation assigned to the Court. The police act as investigators while the prosecutor's office is a public prosecutor, because the Criminal Code Procedure provides different authority. As a result of differences in authority, investigation and interrogation report made by investigators must be examined first before being delegated to the trial. This research is about: (1) how is the authority of the police and prosecutors in the pre-prosecution stage? (2) What is the procedure for the settlement of criminal investigation and interrogation report in pre-prosecution stage at the Denpasar District Prosecutor's Office? This study uses normative legal research methods with sources of primary, secondary and tertiary legal materials. The results of this study can be concluded (1) the authority of the police in the pre-prosecution stage is to conduct an investigation and make a case file. The authority of the prosecutor's office in the pre-prosecution process only checks and examines case files whether the case files made by the investigator have met the terms and conditions of the Criminal Procedure Code. (2) The procedure for settling this case file is carried out by receiving a notification letter on the start of investigation, the appointment of a public prosecutor, research of case files by prosecutors, prosecution, delegation of suspects and evidence, additional inspection by the prosecutor general, transfer of case files, suspects and evidence to court.